Islamic Economic Philosophy: A Philosophical Analysis Of The Digital Consumption Phenomenon From The Perspective Of Maqasid Al-Syariah In Indonesia - Asri Tesi Ramadhani; Syukri Iska; Fandi Ahmad Marlion; Azifah Hidayati (Pascasarjana, Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2026)
This study aims to analyze the concept of consumption in Islamic economics, the phenomenon of Indonesian consumption in the digital era, and its alignment with the principles of Islamic economic philosophy. This study uses the Systematic Literature Review (SLR) method by examining ten scientific articles published between 2020 and 2025 that are relevant to the theme of digital consumption and Islamic values. The selection of these ten articles was based on academic justification based on thematic saturation, which occurs when additional literature no longer produces significant new conceptual themes. This approach was chosen to ensure the representativeness and depth of analysis of the issue of digital consumption in the context of Islamic economic philosophy. The research gap in this study lies in the absence of research that explicitly links Islamic consumption philosophy to the phenomenon of digital consumption through the Maqasid al-Shari'ah framework. The results of the study indicate that consumption in Islamic economics is not merely aimed at satisfying (utility), but is oriented towards achieving maslahah (benefit) and barakah (blessings). The phenomenon of digital consumption in Indonesia shows two extreme poles: increasing awareness of halal (halal) and consumption ethics on the one hand, and consumptive behavior influenced by social media, market algorithms, and digital services on the other. Although digitalization brings convenience and efficiency, digital consumption practices do not fully align with the principles of justice ('adl), moderation (wasathiyah), and benefit (kemaslahah) in Islamic economic philosophy. Therefore, strengthening Islamic economic literacy, digital ethics, and consumption spirituality is necessary to achieve consumption behavior that is just, balanced, and oriented towards the values ​​of maqasid al-Shari'ah